2020
DOI: 10.1057/s41599-020-0510-8
|View full text |Cite
|
Sign up to set email alerts
|

How does the self-sufficiency rate affect international price volatility transmissions in the wheat sector? Evidence from wheat-exporting countries

Abstract: Research on international food prices or volatility transmission have concentrated on importing countries and have largely underestimated the importance of food insecurity or food poverty issues in food-exporting countries. This article identifies the causality between global and regional wheat pric in exporting countries and explores the determinants of price volatility pass-throughs using a Glosten, Jagannathan and Runkle generalised autoregressive conditional heteroskedasticity (GJR-GARCH) model with dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 53 publications
(50 reference statements)
0
19
0
Order By: Relevance
“…This finding implies that large exporters need to protect their own local markets from stormy global markets, which is particularly important for low-income households even in advanced economies such as that of the U.S. Our experiments focused on producer price, but consumer or retail price are correlated with producer price movements. As a matter of fact, it is proved that international price volatility of wheat can be transmitted to retail wheat flour prices in exporting countries (Tanaka and Guo 2020). Hence, large crop-exporting governments such as the U.S. government also need to make policy interventions to segregate retail from foreign markets.…”
Section: Discussionmentioning
confidence: 99%
“…This finding implies that large exporters need to protect their own local markets from stormy global markets, which is particularly important for low-income households even in advanced economies such as that of the U.S. Our experiments focused on producer price, but consumer or retail price are correlated with producer price movements. As a matter of fact, it is proved that international price volatility of wheat can be transmitted to retail wheat flour prices in exporting countries (Tanaka and Guo 2020). Hence, large crop-exporting governments such as the U.S. government also need to make policy interventions to segregate retail from foreign markets.…”
Section: Discussionmentioning
confidence: 99%
“…Guo and Tanaka [7] established a generalized autoregressive conditional heteroskedasticity (GARCH) model with The Ministry of Agriculture, Forestry and Fisheries of Japan aims at increasing the country's food self-sufficiency rate (SSR) for securing food supply against unexpected events (See the MAFF website for further details (https://www.maff.go.jp/e/index.html)). Supply stabilization is closely associated with price stabilization, which directed economists to analyze the relationships between SSR and price co-movement [7][8][9][10]. Thus, a food autarky system has been considered to be an important element for shielding internal markets from uncertain aspects of foreign markets.…”
Section: Introductionmentioning
confidence: 99%
“…Further, we also explore the effects of consumption of potential substitutive goods such as pork and chicken and macroeconomic variables such as GDP per capita growth rate on international price volatility transmissions (i.e., DCCs). Guo and Tanaka [7] and Tanaka and Guo [10] conducted a panel analysis for wheat introducing rice and maize consumption variables as substitutes that could mitigate international spillover effects from global wheat market. Bekkers et al [27] investigated the impacts of GDP per capita on cross-border passthroughs of food prices.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Guo and Tanaka (2019) are the first to employ DCC to examine the relationships between world and local agricultural markets. Tanaka and Guo (2020) also utilised DCC to gauge the efficacy of wheat self-sufficiency policy measures for exporting countries. In addition, to the best of our knowledge, Guo and Tanaka (2020) is the only work that applied a time-varying correlation approach to international beef price passthroughs.…”
mentioning
confidence: 99%
“…Cappiello et al (2006) demonstrated the first application of structural changes to the DCC and asymmetric DCC. However, none of the past price transmission analyses for cereal commodities using the DCC diagnose structural breaks in time-variant correlations (Ceballos et al, 2017;Guo and Tanaka, 2019;Tanaka and Guo, 2020). 1 The present article thoroughly scrutinises the price interconnectivity between world and local beef prices for nine net importing countries, using GARCH-type models with the DCC specification.…”
mentioning
confidence: 99%